KONSEP MINDMAPPING DAN RELEVANSINYA TERHADAP KONEKTIVITAS BELAJAR SISWA - Naura Afkarina; M Jadid Khadavi (Al-Kindi, 2025)
Mindmapping is a visual learning technique that organizes information in a branched and structured thought map. This concept was developed to help students understand, remember, and connect various ideas or learning materials more systematically. This study aims to examine the concept of mindmapping and its relevance to students' learning connectivity the ability to meaningfully link new knowledge with prior understanding. Using a qualitative literature study approach, this research explores various academic sources related to learning theories, visual strategies, and the effectiveness of mindmapping. The findings show that mindmapping stimulates both the right and left brain activities, strengthens memory retention, and enhances the interconnection of concepts in learning. In addition, this technique encourages students to think critically and creatively, fostering a holistic understanding of the material. Therefore, mindmapping is highly relevant as a learning aid that can enhance students' learning connectivity across different educational levels and subjects.